2022
DOI: 10.1038/s41598-022-11485-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community functioning during plant litter decomposition

Abstract: Microbial life in soil is fueled by dissolved organic matter (DOM) that leaches from the litter layer. It is well known that decomposer communities adapt to the available litter source, but it remains unclear if they functionally compete or synergistically address different litter types. Therefore, we decomposed beech, oak, pine and grass litter from two geologically distinct sites in a lab-scale decomposition experiment. We performed a correlative network analysis on the results of direct infusion HR-MS DOM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Our results verified that during the growth and decomposition of phototrophic biofilms, soil DOM universally becomes diversified, but the source-and sitespecific nature of DOM is lost. This finding is consistent with that of Schroeter et al 53 who found that litter metabolomes converged over time in a lab-based decomposition experiment regardless of being derived from different sources. Others working in temperate forests 54 and grasslands 55 have similarly found that DOM from different sources converged as it passed through soils, and this has been attributed to microbial production and consumption of DOM over time.…”
Section: Characterization Of Spe−dom During Biofilm Growth and Decomp...supporting
confidence: 92%
“…Our results verified that during the growth and decomposition of phototrophic biofilms, soil DOM universally becomes diversified, but the source-and sitespecific nature of DOM is lost. This finding is consistent with that of Schroeter et al 53 who found that litter metabolomes converged over time in a lab-based decomposition experiment regardless of being derived from different sources. Others working in temperate forests 54 and grasslands 55 have similarly found that DOM from different sources converged as it passed through soils, and this has been attributed to microbial production and consumption of DOM over time.…”
Section: Characterization Of Spe−dom During Biofilm Growth and Decomp...supporting
confidence: 92%
“…Microbial networks underpin organic matter breakdown 3 , yet their ecology remains in a black box, obscuring our ability to accurately understand and model ecosystem function, resilience and biogeochemical carbon and nutrient budgets. While DNA-based assessments of decomposer microbial communities have occurred in plant litter 4 , 5 and a few in mammals 6 , 7 , little has been revealed about the microbial ecology of how decomposer microbial communities assemble, interact or function in the ecosystem. Our understanding of how animal remains, or carrion, decompose is in its infancy due to the historical focus on plant litter, which dominates decomposing biomass globally.…”
Section: Mainmentioning
confidence: 99%
“…Depending upon the member community, soil microorganisms in tea garden could have beneficial or detrimental effects on tea plants (Figure 1). Beneficial microorganisms, such as members of the Bacillus, Rhizobium, Actinomycetes, Trichoderma, and Glomus promote soil health and enhance plant productivity through improving soil structure and promoting organic matter recycling (Hicks et al, 2021;Wei et al, 2024), e.g., functioning as decomposers of leaf litters and dead plant materials in tea gardens (Schroeter et al, 2022;Wang et al, 2023).…”
Section: Functions Of Soil Microorganisms In Tea Gardensmentioning
confidence: 99%